The Cambridge Companion to Singing - Potter, John (Cambridge Cambridge University Press, 2000)
Ranging from medieval music to Madonna and beyond, this is the only book to cover in detail so many aspects of the voice. The volume is divided into four broad areas. Popular Traditions begins with an overview of singing traditions in world music and continues with aspects of rock, rap and jazz. The Voice in the Theatre includes both opera singing from the beginnings to the present day and twentieth-century stage and screen entertainers. Choral Music and Song features a history of the art song, essential hints on singing in a larger choir, the English cathedral tradition and a history of the choral movement in the United States. The final substantial section on performance practices ranges from the voice in the Middle Ages and the interpretation of early singing treatises to contemporary vocal techniques, ensemble singing, the teaching of singing, children's choirs, and a comprehensive exposition of vocal acoustics.
Keywords: 20th Century (1901-2000); Singing; Vocal music